Development of Mathematical Comic-Strip Application as a Mobile Learning Media-Based Learning - Witri Lestari; Yhohan Ady Chandra (JME (Journal of Mathematics Education), 2018)
The purpose of this study is to develop comic strip media as a learning media for mathematics so that it can create mathematical learning media by utilizing technology or called mobile learning, knowing the steps for developing learning media and designing m-learning learning media designs that are easy for students to understand. as well as knowing the quality of the Mathematical Strip Comic learning media that was developed through three test stages, namely expert validation testing, testing on teacher and student respondents, and evaluation for product revisions. In addition, a research and development development research approach is used in compiling work steps so that conclusions can be drawn that mathematical strips are learning media byutilizing image illustrations in loading the content of teaching materials that can attract students' interest and motivation in learning activities that are easier and more enjoyable. Assessment carried out by media experts, material experts, linguists, teacher respondents, and student respondents found that Comic Strip learning media is in a good category to be used as a support for mathematics learning